A study of intestinal absorption of bicyclol in rats: active efflux transport and metabolism as causes of its poor bioavailability - Tan, Wei; Chen, Hui; Hu, Jinping; Li, Yan (Journal of Pharmacy & Pharmaceutical Sciences, 2008)
Purpose.To determine the possible mechanism of poor bioavailability of bicyclol, and clarify the respective contribution of P- glycoprotein (P-gp) and Cytochrome 3A (CYP3A). Methods. Rat in situ single-pass intestinal perfusion and Caco-2 cell monolayer model with selective inhibitors of CYP3A and P-gp were employed. Results. In rat intestinal perfusion, bicyclol (50µM) appearance in mesenteric blood (Pblood) was increased 3, 12, 16-fold by addition of inhibitors of P-gp (LSN335984), CYP3A ( troleandomycin, TAO) or P-gp and CYP3A (Cyclosporin A, CsA), respectively, whereas permeability of midazolam (CYP3A substrate only) was unchanged by LSN335984 and increased 5 and 1-fold by TAO and CsA. In addition, the metabolized fraction of bicyclol was decreased by 9%, 33%, 36% with inhibitor of P-gp, CYP3A, or P-gp and CYP3A. Moreover, the cumulative amount of bicyclol in mesenteric blood was increased at concentration range 10-100µM of bicyclol in perfusate. The ER (Pappba/Pappab) value of bicyclol in Caco-2 monolayer was significantly deceased by LSN335984 and CsA. Conclusion. The poor bioavailability of bicyclol was mostly due to the P-gp mediated efflux and metabolism by CYP3A in intestine, while CYP3A was believed to make more contribution than P-gp.